Kesalahan dalam Penulisan Proposal Skripsi Mahasiswa di Universitas 17 Agustus Semarang - Andhika Nanda Perdhana; Novita Al Ihyak Dieni (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to identify and analyze the common mistakes made by students in writing thesis proposals in the Education Program of Belief in God Almighty at Universitas 17 Agustus Semarang. The research employed a qualitative approach with a case study design, where data were collected through in-depth interviews, document analysis of thesis proposals, and direct observation. The findings revealed that students frequently struggle with formulating a clear research background, articulating specific research problems, and developing a comprehensive literature review. Additionally, challenges were found in data analysis and the validation of research results. The implications of this study suggest the need for more intensive and structured academic guidance to help students overcome these difficulties and improve the quality of their thesis proposals.